Speed and power-related gene polymorphisms associated with playing position in elite soccer players - Petr, Miroslav; Thiel, Dan; Kateřina, Kvapilová; Brož, Petr; Malý, Tomáš; Zahálka, František; Vostatková, Pavlína; Wilk, Michal; Chycki, Jakub; Stastny, Petr (Biology of Sport, 2022)
Heritability studies on sport-related traits accepted that endurance, speed, power, and strength abilities include an active genetic predisposition to elite soccer participation. This study evaluates the influence of selected genetic variants on performance in speed, power, and strength laboratory tests on a group of elite soccer players, including their playing position. A ninety-nine male elite soccer players were compared to controls (n = 107) and tested for quadriceps and hamstrings isokinetic strength at speed 60°/s, 180°/s, and 300°/s, jump performance, and genotypes of ACTN3 (R577X, rs1815739), ACE (I/D, rs1799752), NOS3 (Glu298Asp, rs1799983), AMPD1 (34C/T, rs17602729), UCP2 (Ala55Val, rs660339), BDKRB2 (+9/-9, rs5810761) and IL1RN (VNTR 86-bp). The ACTN3 XX homozygotes in defenders had lower quadriceps and hamstring isokinetic strength in all tested speeds than ACTN3 RX and RR genotypes (p < 0.05). The ACTN3 RR homozygotes in defenders had higher quadriceps strength in all tested velocities than the RX heterozygotes (p < 0.05). We also found other associations between playing-position in soccer and increased strength of lower limbs for AMPD1 CC and NOS3 Glu/Glu genotypes, and IL1RN*2 allele carriers. Total genetic score regression explained 26% of the variance in jump performance and isokinetic strength. The ACTN3 R allele, NOS3 Glu/Glu genotypes, and IL1RN*2 allele pre-disposed the attackers and defenders playing position in elite soccer, where those positions have higher strength and power measures than midfielders. Midfielders have lower strength and power conditions than other playing positions without relation to strength and power genes.